PENGARUH KARAKTERISTIK CEO, KOMISARIS INDEPENDEN, DAN KUALITAS AUDIT TERHADAP PENGHINDARAN PAJAK - Doho, Sisilia Zealion; Santoso, Eko Budi (Media Akuntansi dan Perpajakan Indonesia, 2020)
This research aims to determine the influence of CEO narcissism, CEO tenure, independent commissioner and audit quality against tax avoidance on companies registered in the non-financial sector. CEO narcissism was measured by scoring the photo of CEO in annual report, CEO tenure was measured from the length of the CEO’s term, independent commissioner was measured by the number of independent commissioners divided by the total commissioner within the company. While audit quality was measured using a dummy variable where score 1 was given was for companies audited by the big four accountant firms and 0 for companies audited by non-big four accountant firms meanwhile the tax avoidance was measured using an ETR proxy. This research used secondary data in fom of annual reports of non-financial sector companies listed on the Indonesia Stock Exchange in the year 2016–2018. The results of this research show that: (1) the CEO of narcissism has no effect on the tax avoidance, (2) the CEO tenure has a significant positive influence on the tax avoidance, (3) independent commissioner has no influence on the tax avoidance, and (4) audit quality has a significant positive influence on the tax avoidance.